PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS BATANGHARI JAMBI - Dina Aunu Rahmah Azhari (SJEE (Scientific Journals of Economic Education), 2023)
This study aims to determine the effect of financial literacy and lifestyle on the consumptive behaviorof Economic Education student at Batanghari University Jambi. The research method used in this study is aquantitative method using multiple linier regression analysis technique. The results showed that there was asignificant positive effect between financial literacy and lifestyle on consumptive behavior in EconomicEducation student at the FKIP Batanghari University Jambi. Thus, partially financial literacy and significanteffect on consumptive behavior in Economic Education students at Batanghari University Jambi.